Analysis of Service Quality on Tax Service Satisfaction - Octavianti, Sweeta; Prastyawan, Agus; Pangaribuan3, Nurmala (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study analyzes the quality of service towards tax service satisfaction. This study includes research using a quantitative approach with an explanatory survey method. The sample required is 40. The instruments in this study are questionnaires and interview guidelines. The method used in data analysis and hypothesis testing in this study is by using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results of the study indicate that the quality of service provided by KPP Pratama Kebayoran Baru Satu is very good so that it is able to provide satisfaction for taxpayers who carry out tax administration at KPP Kebayoran Baru Satu. So that the service system that has been implemented continues to be maintained and even improved so that it is able to provide satisfaction for taxpayers.